P21.1 at PETRA III – a high-energy X-ray diffraction beamline for physics and chemistry - Martin v. Zimmermann; Oleh Ivashko; Fernando Igoa Saldaña; Jiatu Liu; Philipp Glaevecke; Olof Gutowski; Rüdiger Nowak; Katharina Köhler; Björn Winkler; Andreas Schöps; Horst Schulte-Schrepping; Ann-Christin Dippel (Journal of Synchrotron Radiation)
Beamline P21.1 at PETRA III uses high-energy photons for the investigation of materials structure by diffraction methods. The instrumentation is particularly suited for probing ordering phenomena on a local scale in chemistry and physics. A detailed description of the instrumentation and detectors for such experiments is given. The beamline supports a number of sample environments for investigations under in situ and operando conditions, e.g. cryostats, furnaces, chemical reactors. Recent examples of measurements on amorphous, single-crystalline and thin film samples are described.